Evaluation Of Infection Control Planning And Prevention Program Implementation (IPC) At Royal Prima Hospital In 2022 - Seisarita Putri; Ermi Girsang; Sri Lestari Ramadhani; Marlinang Silalahi (International Journal of Health and Pharmaceutical (IJHP), 2022)
As of 2018, a new standard was applied, namely the National Standard for Hospital Accreditation (SNARS) Edition I. IPC is included in the group of Hospital management standards so that a good IPC organizing system can improve the quality of hospital services. The purpose of this study was to assess the IPC of SNARS Edition I. This study used qualitative analysis methods. Specifically, it is comparative descriptive research with a case study design. The object of this research is the implementation of the IPC program which is assessed through surveys and direct observations using the reference of SNARS Edition I. Respondents in this study amounted to 12 people. The search results obtained a PC score of 39.8%. The IPC Team Organization has not been socialized and has not established the IPC program so that surveillance records only run as in the previous year without a report being made to the leadership. The trend of incident cases knowing the management and implementation of the Program with SSI infection tends to increase. Of all the members of the IPC Team, only two members (18.18%) received official IPC education and training from outside the hospital. Existing IPC regulations need to be revised and completed, especially related to infection risk management which will have an impact on improving facilities and infrastructure. The implementation of the IPC program at the Royal Prima Hospital in Medan has not yet reached the graduation rate based on SNARS Edition I.